Reciprocity between agricultural management and productivity in Nawalparasi district - Dhakal, Bhola Nath (Geographical Journal of Nepal, 2019)
Farm management is the making, organizing and operating a farm through the appropriate and timely inputs for maximum production and profit. This paper seeks to explore farm land management practices in-terms of input use in three different sites: Jahada, Palhi and Ramnagar of Nawalparasi district. The paper is based on collected primary data through household questionnaire survey, Focus Group Discussion (FGD), Key Informant Interview (KII) and field observation methods. Secondary sources of data through topographic and cadastral maps have also been used in this study. Use of different types of labour force, increasing the input use of manure, chemical fertilizers and pesticides, use of modern machineries, development of irrigation facilities, land intensification and crop diversification are the major strategies for agricultural development adopted by local peoples in the study sites.